Economic Benefits from Managing Coffee Berry Borer (Hypothenemus hampei) in Hawaii - Donna Lee; Melissa A. Johnson; Luis F. Aristizábal; Suzanne Shriner; Catherine Chan; Susan Miyasaka; Marisa Wall (Insects, 2023)
Coffee berry borer (CBB) is considered the most damaging insect pest of coffee worldwide. CBB was first detected on Hawai‘i Island in 2010, and quickly spread throughout the state’s coffee-growing regions. With the introduction of this pest, Hawaii’s small yet economically important coffee industry was changed forever with growers facing significantly higher production and labor costs, as well as decreased yield and coffee quality. We assessed the economic benefits of managing CBB based on three strategies that emerged in Hawaii over the last decade: (1) the use of the entomopathogenic fungus Beauveria bassiana alone, (2) early integrated pest management (IPM), which combined monitoring and sanitation with spraying B. bassiana, and (3) research-based IPM, which focused on CBB biology in Hawaii, optimization of monitoring, B. bassiana applications, and cultural controls. From 2011 to 2021, the economic benefits from managing CBB were USD 52 million using B. bassiana alone, USD 69 million from early IPM, and USD 130 million from research-based IPM, for a total of USD 251 million from all management. Our findings suggest that all types of management provide economic benefits to Hawaii growers, but management strategies based on Hawaii-specific research have provided the greatest gains in coffee yield, price, and revenue.